2018
DOI: 10.1159/000492632
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Aphasia in NeuroDegeneration for the Diagnosis of Patients with Primary Progressive Aphasia: Clinical Validity and Psychometric Properties

Abstract: Background: We evaluated the psychometric proprieties of the Screening for Aphasia in NeuroDegeneration (SAND) battery in Italian primary progressive aphasia (PPA) and movement disorder (MD) patients. Methods: The sample included 30 consecutive PPA and 45 MD patients who completed the SAND battery together with a clinical interview and a neurological/neuropsychological examination and 130 healthy controls (HC). Results: The SAND battery showed good internal consistency and good convergent and divergent validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…The present study showed that the PSP-tailored SAND battery is acceptable, reliable, and easily applicable to PSP patients. By removing subscores with high proportion of missing values and expanding subscores of the remaining tasks, we used the best combination of SAND tasks to screen language ability in PSP leading to a significant improvement in consistency and acceptability as compared to the original SAND Global Score [5,15]. As a matter of fact, differently from patients with PPA, PSP patients disclose peculiar clinical features possibly impacting performances on specific language tasks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study showed that the PSP-tailored SAND battery is acceptable, reliable, and easily applicable to PSP patients. By removing subscores with high proportion of missing values and expanding subscores of the remaining tasks, we used the best combination of SAND tasks to screen language ability in PSP leading to a significant improvement in consistency and acceptability as compared to the original SAND Global Score [5,15]. As a matter of fact, differently from patients with PPA, PSP patients disclose peculiar clinical features possibly impacting performances on specific language tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study showing a cut off for a language battery differentiating PSP from PD and HC. Previous evidence showed the SAND cut off of 5 was able in differentiating PPA from patients affected by movement disorders (PD and PSP)[5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activities of daily living were preserved. At the speech-language examination, he showed isolated semantic deficits, ie, impairment in single-word comprehension, nonverbal semantic association, surface dyslexia and word-finding difficulties as assessed by the Screening for Aphasia in Neurodegeneration battery (SAND) 10,11. At the spontaneous speech task, he showed a low speech rate associated with several false starts and a lot of lexical-semantic errors, ie, word-finding pauses with a tendency to produce high-frequency nouns and poor content resulting in a reduction of information units.…”
Section: Case Reportmentioning
confidence: 99%